Using future food demand estimates to inform food policy planning in Kenya - Song, Chun; Yego, Francis; Petsakos, Athanasios; Gotor, Elisabetta (2025)
• National food demand projections often hide differences in food demand across counties, which are important for targeted food system planning at the local level to ensure food security. • We use downscaled future food demand projections in Kenya to show how these estimates can support Kenya food policy at the local level. • Kenyan counties demonstrate different patterns of demand for dietary diversity in the future. • Ensuring food supply for areas with increasing demand of diverse food remain a challenge.